Author response to: Clean Cut (adaptive, multimodal surgical infection prevention programme) for low-resource settings: a prospective quality improvement study. Issue 3 (16th March 2021) - Forrester, Jared A; Starr, Nichole; Gebeyehu, Natnael; Negussie, Tihitena; Weiser, Thomas G
Abstract : response to commentary